2007
DOI: 10.1063/1.2749404
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties of spin-reorientation transitions in orthoferrites

Abstract: Magnetic and structural characteristics of ErFeO3, TmFeO3, and YbFeO3 single crystals were studied over a wide temperature range. Magnetic measurements found that the spin-rotation transitions in all crystals are well described by the earlier proposed theory with no fitting parameters. Additionally, they have shown the absence of the magnetic compensation point in TmFeO3 and a noticeable growth of the c-axis magnetization at low temperatures in TmFeO3 and ErFeO3. The x-ray measurements found no symmetry-loweri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…In the recent years, rare-earth orthoferrites RFeO 3 (where R is a rare-earth ion) have attracted much interest due to their novel magnetic [1,2] and magneto-optic [3,4] properties and are still the subject of much research aimed at a better understanding of properties of the magnetic subsystems and how interactions between them depend on external parameters, such as temperature, field, pressure, etc. [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, rare-earth orthoferrites RFeO 3 (where R is a rare-earth ion) have attracted much interest due to their novel magnetic [1,2] and magneto-optic [3,4] properties and are still the subject of much research aimed at a better understanding of properties of the magnetic subsystems and how interactions between them depend on external parameters, such as temperature, field, pressure, etc. [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…10 Spin reorientation is another attractive characteristic of RFeO 3 , in which the direction of the easy axis of magnetization changes from one crystal axis to another. 11,12 The following three types of G-type antiferromagnetic (AFM) configurations can be observed for orthoferrites: C 1 ðA x ; G y ; C z Þ, C 2 ðF x ; C y ; G z Þ, and C 4 ðG x ; A y ; F z Þ, following the Bertaut notation. 13 C 4 is the basal magnetic structure of Fe 3þ just below the Neel temperature, T N , which is a canted AFM structure with a total ferromagnetic (FM) vector F directed along the c (c//z) crystal axis, and an AFM vector G directed along the a (a//x) crystal axis.…”
mentioning
confidence: 99%
“…Orthoferrites RFeO 3 (where R is a rare-earth ion) are noncollinear antiferromagnets with unique magnetic properties, such as spin reorientations and rare-earth moment orders at low temperatures [1][2][3][4]. The origin of this complex magnetic behavior lies in the existence of two magnetic ions, Fe and rare-earth, their mutual interactions, and the peculiarities of the single ion anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…This container-free technique has become a preferred growth method for various classes of oxides and intermetallics, especially for those showing extreme melt reactivity and high melting temperature [12]. Although many groups reported the magnetic and multiferroic properties of single crystals of orthoferrites grown by the floating zone method, they did not give details of the actual growth conditions or the qualities of the crystals used [4][5][6][7][8]. Koohpayeh et al reported the influence of growth rate on the microstructural magnetic properties of floatzone grown ErFeO 3 crystals [13].…”
Section: Introductionmentioning
confidence: 99%